Anti-staphylococcal activity of a polyphenol-rich citrus extract: synergy with β-lactams and low proficiency to induce resistance - Mazzantini, Diletta; Massimino, Mariacristina; Calvigioni, Marco; Rossi, Virginia; Celandroni, Francesco; Lupetti, Antonella; Batoni, Giovanna; Ghelardi, Emilia (Frontiers in Microbiology, 2024)
Antibiotic resistance represents one of the most significant threats to public health in the 21 st century. Polyphenols, natural molecules with antibacterial activity produced by plants, are being considered as alternative antimicrobial strategies to manage infections caused by drug-resistant bacteria. In this study, we investigated the antibacterial activity of a polyphenol mixture extracted from citrus fruits, against both antibiotic-susceptible and resistant strains of Staphylococcus aureus and Staphylococcus epidermidis. Broth microdilution and time-kill curve experiments were used to test the extract antistaphylococcal activity. Cytotoxicity was assessed by the hemolysis assay. The interaction between the mixture and antibiotics was investigated by the checkerboard assay. The effect of B alone and in combination with oxacillin on the membrane potential was investigated by the 3,3′dipropylthiadicarbocyanine iodide assay. The ability of the extract to induce the development of resistance was verified by propagating S. aureus for 10 transfers in the presence of sub-inhibitory concentrations. The citrus extract was found to be active against all Staphylococcus strains at remarkably low concentrations (0.0031% and 0.0063%), displaying rapid bactericidal effects without being toxic on erythrocytes. In particular, B was found to rapidly cause membrane depolarization. When combined with methicillin, meropenem, and oxacillin, the mixture displayed synergistic activity exclusively against methicillin-resistant strains. We additionally show that the sequential exposure of S. aureus to sub-inhibitory concentrations did not induce the development of resistance against the extract. Overall, these findings support the potential use of the citrus extract as promising option to manage staphylococcal infections and suggest that it may counteract the mechanism behind methicillin-resistance.